Peran bank syariah dalam berbagai aspek bagi masyarakat Indonesia - Izzun Khoirun Nissa; M. Dhzuhri (Jurnal Rekoginisi Ekonomi Islam, 2022)
The writing of this article reviews the role of Islamic banks for the people of Indonesia as the main subject of discussion. However, it does not only focus on one discussion, but matters relating to the role of Islamic banks in Indonesian society will be more or less conveyed. It aims to complement information related to the role of Islamic banks in Indonesia. It is certain that banks with basic sharia principles are needed by the people of Indonesia, the majority of which are Muslims. Not only that, the basic principles of Islamic banking, if dissected, will be more conscientiously liked by the Indonesian people in general, because the basis of justice, togetherness and mutual benefit are the basis for the implementation of service products in Islamic banks. Even if compared briefly with conventional banks , then it is as if conventional banks are superior in profit taking, but if studied in depth, Islamic banks will provide greater benefits. In terms of the religious and cultural aspects of Indonesian society, the basic principles of Islamic banking are more suitable than conventional banks. The elements of togetherness, justice and kinship that are thick with the Indonesian people are closely related to the basic principles of Islamic banking.